TRANSFORMING THE POST-MUWAḤḤIDDŪN MAN: MALIK BENNABI’S CRITIQUE OF THE CONTEMPORARY MUSLIM SOCIETY - Muhammad Yusuf Patria (Universitas Muhammadiyah Yogyakarta, 2021)
This article is aimed at discussing the critical analysis of a Muslim thinker, Malik Bennabi, of the state of contemporary Muslim society. This discussion uses a descriptive-analytic approach with Bennabi's works as the primary source and other supporting works as secondary sources. Bennabi's definition of a society, especially its origin, basic elements, and its stages, is described in detail as a basis for understanding Bennabi's thoughts. then, the article discusses Bennabi's analysis and criticism of the current state of Muslim society. For him, the root of all the problems experienced by Muslim society today is an internal weakness or what he calls